Floods and reservoir safety (Thomas Telford, 1996)
Taking into account the research and reflecting the experience of engineers in this field, this book provides guidance on flood protection standards, flood magnitude and freeboard - guidance which is essential for engineers who are responsible for the design and inspection of reservoirs.